2022
DOI: 10.1002/adfm.202110580
|View full text |Cite
|
Sign up to set email alerts
|

4D Printing of Shape Memory Polymers: From Macro to Micro

Abstract: A novel and versatile shape memory ink system allowing 4D printing with light at the macroscale as well as the microscale is presented. Digital light processing (DLP) and direct laser writing (DLW) are selected as suitable 3D printing technologies to cover both regimes. First, a system based on monofunctional isobornyl acrylate and two crosslinkers consisting of a soft and a hard diacrylate is identified and proven to be compatible with both printing techniques. Employing DLP, a large variety of structures exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 63 publications
0
80
0
6
Order By: Relevance
“…Comparatively, shape memory polymers (SMPs) feature the advantages of large deformation, light weight, strong recovery stress, and fast response rates, and thus they play a principal role in 4D printing for various applications. [30][31][32][33][34] For instance, Zarek et al reported 4D printing of SMPs network and employed them for the construction of responsive flexible electronic devices. [35] A series of photo-curable SMPs were utilized to achieve multimaterial 4D printing, and the resulting geometries exhibited time-dependent sequential shape recovery dramatically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, shape memory polymers (SMPs) feature the advantages of large deformation, light weight, strong recovery stress, and fast response rates, and thus they play a principal role in 4D printing for various applications. [30][31][32][33][34] For instance, Zarek et al reported 4D printing of SMPs network and employed them for the construction of responsive flexible electronic devices. [35] A series of photo-curable SMPs were utilized to achieve multimaterial 4D printing, and the resulting geometries exhibited time-dependent sequential shape recovery dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, shape memory polymers (SMPs) feature the advantages of large deformation, light weight, strong recovery stress, and fast response rates, and thus they play a principal role in 4D printing for various applications. [ 30–34 ] For instance, Zarek et al. reported 4D printing of SMPs network and employed them for the construction of responsive flexible electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these technologies could work synergistically with other functional resists fabrication of functioning MEMS devices intrinsically capable of responding to external stimuli, [ 14,15 ] sensing, [ 16 ] show enhanced properties, [ 17–19 ] controlled actuation, [ 20,21 ] and shape recovery. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these technologies could work synergistically with other functional resists fabrication of functioning MEMS devices intrinsically capable of responding to external stimuli, [14,15] sensing, [16] show enhanced properties, [17][18][19] controlled actuation, [20,21] and shape recovery. [22] Few solutions were proposed recently to bring subtractive manufacturing to DLW. Oxygen plasma, for example, can effectively remove thin structures, [13,23] but, by acting on the entirety of the structure, lacks sensitivity and thus requires optimization of the different printing parameters to obtain the desired design.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] As a result, AM is making progress in various industrial and emerging applications, including biomedical, electrical energy storage, electronics, and so on. [13][14][15][16][17][18][19] Compared to conventional manufacturing techniques such as molding, vat (photo-curing) photopolymerization is one of the widely employed additive manufacturing process technologies due to its high precision, [20][21][22] low energy consumption, and nonpollution advantages, [16,[23][24][25] especially with the development of reversible deactivation radical polymerizations (RDRP). [26][27][28][29][30][31][32] Further developments in resin composition or formulation may lead to advances in potential 4D printing.…”
Section: Introductionmentioning
confidence: 99%